Gender violence in Portugal: discourses, knowledge and practices - Mariana Azambuja (2013)
This article discusses the emergence of feminism in Portugal with special emphasis on the actions taken in confronting gender violence. Starting with the history of feminist movements and its implications for the development of the country, it maps public policies, legal measures and victim support institutions/services to better understand the phenomena of violence against women and to identify strategies, adopted in the last decades, to confront it. Presenting a synthesis of some Portuguese studies on women and violence, this article mirrors the increasing interest in the study of violence against women in the academic context and especially in the context of gender studies.